Full mouth periodontal debridement with or without adjunctive metronidazole gel in smoking patients with chronic periodontitis: A pilot study - Bergamaschi, C. C.; Santamaria, M. P. [UNESP]; Berto, L. A.; Cogo-Mueller, K.; Motta, R. H. L.; Salum, E. A.; Nociti Junior, F. H.; Goodson, J. M.; Groppo, F. C. (Wiley-Blackwell, 2016)
Background and ObjectiveThe evidence of effectiveness of metronidazole (Mtz) as an adjunct therapy to periodontal procedure in the treatment of patients with chronic periodontitis is not conclusive. The aim of this study was to compare the effect of Mtz (delivered locally as a gel or systemically as a tablet) as an adjunctive therapy with full mouth periodontal debridement (1h of ultrasonic calculus/plaque removal) in smokers with chronic periodontitis. Material and MethodsThis pilot study involved 30 smokers with at least six teeth with a clinical attachment loss of 5mm and probing pocket depth (PPD) of 5mm. They were randomly assigned into one of three groups (n=10): (i) 3g daily of placebo gel applied topically (using a dental tray with the gel overnight) + periodontal debridement; (ii) 3g daily of a 15% Mtz benzoate gel applied topically (using a dental tray with the gel overnight) + periodontal debridement; and (iii) a daily single dose of 750mg Mtz (Flagyl((R))) + periodontal debridement. Clinical parameters (visible plaque index, gingival bleeding index [GBI], relative attachment level and PPD) and quantitative analysis (by real-time polymerase chain reaction) of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis and Tannerella forsythia were assessed at baseline and at 1, 3 and 6mo after periodontal debridement. ResultsThere was no statistically significant difference in the average GBI and visible plaque index values at baseline between the groups (p0.05). There was no significant difference between groups in all parameters evaluated (p0.05). Significant reductions in GBI at 3 and 6mo were observed in all groups (p<0.05). Significant reductions in both PPD and relative attachment level at 1, 3 and 6mo were observed in all groups (p<0.05). Significant reductions in bacterial levels at 7 and 30d were observed in all groups (p<0.05). ConclusionAdjunctive use of Mtz (gel or tablet) to periodontal debridement had similar clinical and microbiological improvement compared to treatment with placebo + periodontal debridement in smokers with chronic periodontitis up to 6mo post-treatment. Further studies are necessary to confirm the clinical relevance of these findings.
Keywords: adjunctive periodontal therapy; metronidazole; periodontitis; smoking